B Cells use Conserved Polarity Cues to Regulate Their Antigen Processing and Presentation Functions - Yuseff, Maria-Isabel; Lennon-Duménil, Ana Maria (Frontiers in Immunology, 2015)
The ability of B cells to produce high-affinity antibodies and to establish immunological memory in response to a wide range of pathogenic antigens is an essential part of the adaptive immune response. The initial step that triggers a humoral immune response involves the acquisition of antigens by B cells via their surface immunoglobulin, the B cell receptor (BCR). BCR-engaged antigens are transported into specialized lysosomal compartments where proteolysis and production of MHC class II peptide complexes occur, a process referred to as antigen processing. Expression of MHC class II complexes at the B cell surface allows them to interact with T cells and to receive their help to become fully activated. In this review we describe how B cells rely on conserved cell polarity mechanisms to coordinate local proteolytic secretion and mechanical forces at the B cell synapse enabling them to efficiently acquire and present extracellular antigens. We foresee that the mechanisms that dictate B cell activation can be used to tune B cell responses in the context of autoimmune diseases and cancer.